Nursing spiritual assessment instruments in adult patients: a narrative literature review - Cosentino, Chiara; Harrad, Rachel A.; Sulla, Francesco; Bertuol, Maria; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Spiritual care in nursing is a critical part of providing holistic care. Whilst patients might desire spiritual care and value the opportunities that nurses take to engage with them to meet their spiritual needs, research suggests that nurses do not consistently engage in spiritual care with their patients. To identify instruments available to nurses to assess spirituality in different patient groups and highlight the characteristics and psychometric properties of these instruments. Method: A narrative literature review of the relevant literature published after 2008 was carried out in CINAHL, PsycINFO, MEDLINE and Google scholar databases in October 2020. Narrative review synthesized key findings and grouped instruments into macro areas by content. Results: After the screening, based on inclusion criteria, 31 articles were identified. 17 instruments were identified and divided into 4 macro areas: wellbeing (N = 4), attitude (N = 5) needs (N =6) and multiple domains (N = 2). Conclusions: This review enables an increased awareness of the variety of instruments available to aid spiritual care and therefore increase their use within nurse clinical practice. The widening of the patient group to be considered (i.e., non-oncological) may have a significant impact on the practice, causing professionals to reflect on the necessity to investigate spiritual needs even at an early stage of a disease process. Future studies should aim to test reliability and validity of existing instruments rather than develop further ones.